2020
DOI: 10.21203/rs.3.rs-25100/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hypertension prevalence, awareness, treatment, and control and predicted 10-year CVD risk: a cross-sectional study of Seven Communities in East and West Africa (SevenCEWA)

Abstract: Background: Few studies have characterized epidemiology and management of hypertension across several communities with comparable methodology in sub-Saharan Africa. We assessed prevalence, awareness, treatment, and control of hypertension and predicted 10-year cardiovascular disease risk across seven sites in East and West Africa. Methods: Between June and August 2018, we conducted household surveys among adults aged 18 years and above in 7 communities in Kenya, Nigeria, Tanzania, and Uganda. We collected data… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
1
2
Order By: Relevance
“…This prevalence of controlled hypertension of 39.7% is similar to the study done at Muhimbili National Hospital of Tanzania in 2013 assessing hypertension control which showed control rate of 34%. [16] However the prevalence of controlled hypertension found in this study was higher than the study done in 2020 by Alfa Muhihi et al involving seven communities of East and West Africa in sub-Saharan Africa which showed that among participants with prevalent hypertension, 13% had their blood pressure controlled, [17] Also the study done in Ghana in 2018, in which the prevalence of blood pressure control was 23.8% among of patients taking anti-hypertensive medication [18] .…”
Section: Discussioncontrasting
confidence: 57%
“…This prevalence of controlled hypertension of 39.7% is similar to the study done at Muhimbili National Hospital of Tanzania in 2013 assessing hypertension control which showed control rate of 34%. [16] However the prevalence of controlled hypertension found in this study was higher than the study done in 2020 by Alfa Muhihi et al involving seven communities of East and West Africa in sub-Saharan Africa which showed that among participants with prevalent hypertension, 13% had their blood pressure controlled, [17] Also the study done in Ghana in 2018, in which the prevalence of blood pressure control was 23.8% among of patients taking anti-hypertensive medication [18] .…”
Section: Discussioncontrasting
confidence: 57%
“…This prevalence of controlled hypertension of 39.7% is similar to the study done at Muhimbili National Hospital of Tanzania in 2013 assessing hypertension control which showed control rate of 34%. [16] However the prevalence of controlled hypertension found in this study was higher than the study done in 2020 by Alfa Muhihi et al involving seven communities of East and West Africa in sub-Saharan Africa which showed that among participants with prevalent hypertension, 13% had their blood pressure controlled, [17] Also the study done in Ghana in 2018, in which the prevalence of blood pressure control was 23.8% among of patients taking anti-hypertensive medication [18] . Similarly, a study done in ruraldwelling Tanzanian older adults in 2012 reported a prevalence of controlled hypertension of 14.9% of those on regular treatment and 0.9% of all hypertensives.…”
Section: Discussioncontrasting
confidence: 52%
“…A study recruiting individuals from a rural community in Sudan found the prevalence of undiagnosed hypertension of about 38.2%, 13 a similar study in Nigeria among market traders, 14 and to another study, where the prevalence of undiagnosed hypertension was 42.8%. 6 The variation in the study results may be due to the differences in the study population as our study was done in urban market where majority of the study participants were possibly more aware about their health status. Secondly, the low consumption of fats and sugar and high consumption of vitamins among our respondents that may explain a healthy diet which is protective for hypertension.…”
Section: Discussionmentioning
confidence: 93%
“…This number is projected to rise to 216.8 million by the year 2030 (66% rise from the year 2010). 6 In sub-Saharan Africa, the total number of individuals with hypertension was estimated to be 75 million in 2008 and projected to be at 125.5 million by 2025. 7 There is a high burden of hypertension in Africa; however, over three-quarters of the cases are unaware they have hypertension.…”
Section: Introductionmentioning
confidence: 99%